2014
DOI: 10.5173/ceju.2014.01.art2
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic radical cystectomy: neobladder or ileal conduit, debate still goes on

Abstract: ObjectiveTo compare the pre, intra, and post–operative data between ileal conduit and neobladder urinary diversions during laparoscopic radical cystectomy(LRC).Material and methodsBetween 2006 and 2011, 63 patients who underwent LRC and urinary diversion had their data input prospectively into a database and said data used for the analysis. The outcome comparators were the patient demographics, operative time, conversion rate, blood loss, transfusion rate, morphine analgesic requirement, length of hospital sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Of the potentially eligible studies, six were excluded, as they were not RCTs; one study was a protocol for an on-going study. Aboumarzouk et al [ 31 ] compared 155 patients undergoing LRC or ORC retrospectively. Aboumohamed et al [ 30 ] reported retrospective data from patients undergoing radical cystectomy.…”
Section: Resultsmentioning
confidence: 99%
“…Of the potentially eligible studies, six were excluded, as they were not RCTs; one study was a protocol for an on-going study. Aboumarzouk et al [ 31 ] compared 155 patients undergoing LRC or ORC retrospectively. Aboumohamed et al [ 30 ] reported retrospective data from patients undergoing radical cystectomy.…”
Section: Resultsmentioning
confidence: 99%
“…However it is worth bearing in mind that each type of urinary diversion has inherently different challenges associated with it. 6 According to meta-analysis there is a higher rate of UTI in the orthotopic neobladder group, potentially as orthotopic neobladders often require self-catheterisation which comes with the associated risk of bacterial inoculation. 35 Meta-analysis also demonstrated a significantly higher risk of ureteroileal stricture in patients with an orthotopic neobladder than those with an ileal conduit urinary diversion, possibly due to the use of an anti-reflux mechanism in ureterointestinal anastomosis, however an antireflux mechanism was only used for ONB in two of the publications included in this review.…”
Section: Cuaj -Reviewmentioning
confidence: 99%